Land clearing for agricultural research stations: IITA research guide, No. 5 - Couper, D.C. (1994)
Large areas of land are presently cleared of their natural cover, endangering the worldwide ecosystem. Land clearing, if necessary, should be carried out with great care after very careful consideration. Different land types require different clearing techniques. Often, soil needs to be stabilized after clearing. All clearing processes require training of persons involved.